2007
DOI: 10.1128/aem.02302-06
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Engineering of Zymobacter palmae for Production of Ethanol from Xylose

Abstract: Its metabolic characteristics suggest that Zymobacter palmae gen. nov., sp. nov. could serve as a useful new ethanol-fermenting bacterium, but its biotechnological exploitation will require certain genetic modifications. We therefore engineered Z. palmae so as to broaden the range of its fermentable sugar substrates to include the pentose sugar xylose. The Escherichia coli genes encoding the xylose catabolic enzymes xylose isomerase, xylulokinase, transaldolase, and transketolase were introduced into Z. palmae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 25 publications
0
31
1
Order By: Relevance
“…After metabolic adaptation in xylose-containing medium, the microorganism reached 95% efficiency from the fermentation of glucose and xylose [12], higher than the efficiency reported in the study by Mohagheghi et al [13], who achieved 76% efficiency with the use of 75% (v/v) of the pentose-derived hemicellulosic hydrolysate by Z. mobilis. Thus, Zhang et al [14] demonstrated that the co-expression of XI, XK, TAL and TKT, derived from Escherichia coli, allowed Z. mobiles to coferment xylose and glucose, reaching 11 g/L ethanol and resulting in a yield of 0.44 g ethanol/g xylose consumed.…”
Section: Application Of Genetic Engineering In Z Mobilis Cellscontrasting
confidence: 40%
See 2 more Smart Citations
“…After metabolic adaptation in xylose-containing medium, the microorganism reached 95% efficiency from the fermentation of glucose and xylose [12], higher than the efficiency reported in the study by Mohagheghi et al [13], who achieved 76% efficiency with the use of 75% (v/v) of the pentose-derived hemicellulosic hydrolysate by Z. mobilis. Thus, Zhang et al [14] demonstrated that the co-expression of XI, XK, TAL and TKT, derived from Escherichia coli, allowed Z. mobiles to coferment xylose and glucose, reaching 11 g/L ethanol and resulting in a yield of 0.44 g ethanol/g xylose consumed.…”
Section: Application Of Genetic Engineering In Z Mobilis Cellscontrasting
confidence: 40%
“…Therefore, although improvements regarding fermentation with this genetically modified Z. mobilis are still needed, the fermentation time and the ability to ferment xylose were both improved. Figure 3 summarizes the metabolic adaptation process insynthetic medium, suggesting that the recombinant Z. mobilis colonies increased ethanol production in the earlier cycles (1-30)but maintained such levels in subsequent cycles (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). This strategy allowed the recombinant to produce ethanol from xylose more efficiently becausehigher participation in ethanol production is derived from this pentose in the latter cycles.…”
Section: Metabolic Adaptation In Synthetic Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, efforts have been made to obtain recombinant strains of bacteria and yeast able to meet the requirements of industrial lignocellulose fermentation. Escherichia coli, Klebsiella oxytoca and Zymomonus mobilis have all been genetically engineered to produce ethanol and biofuel efficiently from all hexose and pentose sugars present in the polymers of hemicellulose (Attfield and Philip, 2006;Hahn-Hagerdal et al, 2007;Kim et al, 2007;Yanase et al, 2007). Others mentioned in the literature included Klebsiella species, Pichia stipitis, Bacillus species and Kluveromyces species.…”
Section: Pentose-fermenting Microorganisms and Potential Productsmentioning
confidence: 99%
“…A strain of Zymobacter palmae was engineered to express xylose catabolic enzymes intracellularly, and produce approximately 45 g/l of ethanol from pure xylose [45]. The ability of the strain to utilize corn starch or more complex carbohydrates as a carbon source was not explored.…”
Section: Surface-display For Biofuels Productionmentioning
confidence: 99%